“[…] the Monstrous System of Laokiun:” Kant and the Eastern Philosophies of Unity - Pissis, Jannis (Ariadne, 2026)
The paper examines Kant’s references to the philosophy of the East. On the one hand, it explores Kant’s lectures where he discusses the pre-Greek beginnings of philosophy. An attempt is made to defend Kant against the suspicion that he was responsible for the exclusion of African and Asian thought from the philosophical canon, an exclusion that took place around 1800. In particular, it is argued that Kant’s conception of an ‘a priori history of philosophy’ is not structurally Eurocentric/Grecocentric, and that Kant’s shift towards Grecocentric positions in his later lectures is not systematically intertwined with that conception. On the other hand, the paper discusses Kant’s reference to Daoism, Buddhism and other Eastern views in his essay “The End of All Things” of 1794. It is shown that the reference is not merely dismissive and that Kant’s philosophy can be open to a dialogue with non-European traditions.